Homemade Drink / Mohamad Fikry Aizat Mohammed Fauzi - Mohammed Fauzi, Mohamad Fikry Aizat (2021)
Homemade Drink is a small F&B business that based on Sungai Buloh. Homemade Drink is a partnership company owned by a Fikry and Tzuyu. The main platform we use to sells and updates about our product is on Facebook. The customer can contact directly with the company by using WhatsApp. The product that we sells is homemade drink that use natural ingredient and without artificial sweetener. Our company offer 3 different flavor that will make you guys love which is Bandung Soda, Jagung and Kateera. All of our drink is very refreshing, rehydrating and cooling. This drink is popularly served during the month of Ramadhan when it is time to break the fast for the day. Our signature and the most demanded drink is Kateera. This fabulous drink sweetened with sugar syrup will inspire guests to linger for one more glass. You'll be amazed at the pleasing flavors that pop out when you combined katira (gond katira), basil seed, kembang semangkok (malva nuts) with evaporated milk. Homemade Drink updates their Facebook post about the product that we sells regularly to attract more potential customer. We communicates with our customer using Facebook messenger and WhatsApp. For now we only promote it on Facebook and sells it through cash on delivery. We don’t deliver our product to other cities using courier service because it may damage the product since this drink need to be always refrigerated.